Organizational justice and motivation on employee performance: Moderating role of commitment - Rahmisyari Rahmisyari; Nursia Daeng Salasa; Juriko Abdussamad; Joko Tri Brata (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the effect of Organizational Justice Perception and Work Motivation on Employee Performance, with Organizational Commitment as a moderating variable, at the Health Office of South Bolaang Mongondow Regency, Indonesia. A quantitative survey was conducted among 162 employees selected through proportional stratified random sampling from a population of 270, and the data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The model explains 48.5 percent of the variance in Employee Performance. Organizational Justice Perception (β = 0.415; t = 5.324; p = 0.000) and Work Motivation (β = 0.193; t = 2.655; p = 0.008) both have significant positive effects on Performance, and Organizational Commitment also has a direct positive effect (β = 0.254; t = 3.163; p = 0.002). Organizational Commitment significantly moderates the justice-performance relationship, but in a weakening rather than strengthening direction (β = -0.161; t = 1.992; p = 0.046), while its moderating role on the motivation-performance relationship is not significant (β = 0.054; t = 0.803; p = 0.422). These findings extend the literature by showing that the moderating role of organizational commitment is contingent on its dominant dimension and organizational context, offering practical direction for improving distributive justice in performance-based allowance schemes.